Influence of Water-jet Nozzle Geometry on Cutting Ability of Soft Material - Irwansyah, Irwansyah; Ibrahim, Masri; Ferdiansyah, Hendra (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Hygiene is main reason for food processor to use waterjet cutting system. Traditionally food cutting process is low-quality, unsafe products, procedures and direct contact between product and labor. This paper introduced a low cost waterjet system for cutting soft material as identic food material. The low cost waterjet system has been developed by using a commercial pressure pump for cleaning purposes and modified nozzle. In order to enhance waterjet pressure for cutting products, a modified waterjet nozzle was designed. Paramater design of waterjet system was setup on nozzle orifice diameter 0.5 mm, standoff distance 15 mm, length of nozzle cylindrical tube 2.5 mm. Polycarbonate, polysterene, and polyethelene materials are used as sample product with thickness 2 mm, to represent similar properties with agriculture products. The experimental results indicate good possibilities of waterjet system to cut material in appropriate profile surface. The waterjet also can be used to improve cutting finished surface of food products. Therefore, utilizing a low cost commercial pump and modified nozzle for waterjet system reduces equipment price, operational cost and environmental hazards. It indicates viable technology applied to substitute traditional cutting technology in post harvest agriculture products.Keywords: cutting ability, modified nozzle, polymer material, water-jet system